Comparison of 10 and 14 days of triple therapy versus 10 days of sequential therapy for Helicobacter pylori eradication: A prospective randomized study - Ennkaa, Abulgasim; Shaath, Nabeel; Salam, Abdul; Mohammad, Ramzi M. (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: The aim of the present study was to compare between the efficacy and tolerability of a sequential therapy (ST) as the first-line treatment for adults with Helicobacter pylori infection and that of standard triple therapy (TT). Materials and Methods: This was a prospective, randomized open-label, single-center study. We enrolled 206 patients who were divided into the following three treatment groups: Group A (pantoprazole 40 mg bid (twice daily), amoxicillin 1 g bid, and clarithromycin 500 mg bid for 10 d), Group B (the same TT as Group A for 14 d), and Group C (pantoprazole 40 mg bid and amoxicillin 1 g bid for 5 d, followed by pantoprazole 40 mg bid, clarithromycin 500 mg bid, and metronidazole 500 mg bid for additional 5 d). Results: Intention-to-treat (ITT) analysis revealed that 14 d of TT achieved a higher eradication rate than 10 d of ST (54.8% vs. 50.7%), but the difference was not statistically significant (p=0.623); further, 10 d of TT achieved 45% eradication rate. Per-protocol (PP) analysis revealed that the success rate for 10 d of ST was more than that for 10 d of TT (70.6% vs. 65%; p=0.571); however, the success rate for 10 d of TT was not statistically different from that for 14 d of TT. The eradication rates achieved in the ITT analysis were lower than those achieved in the PP analysis for 10 (45% vs. 65%) or 14 (54.7% vs. 69%) d of TT or for 10 d of ST (50.7% vs. 70.6%). No statistically significant difference was observed. Adverse effects and compliance were not significantly different among the three groups. Conclusion: Neither 10 d of ST nor 14 d of TT achieved the optimum H. pylori eradication rate. Cite this article as: Ennkaa A, Shaath N, Salam A, Mohammad RM. Comparison of 10 and 14 days of triple therapy versus 10 days of sequential therapy for Helicobacter pylori eradication: A prospective randomized study. Turk J Gastroenterol 2018; 29: 549-54.